(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
Literary work is the result of creative works, human creations that display expressive, imaginative, aesthetic, understanding and responses to the feelings of the author about the life of his imagination, which cannot be separated from the life of society. The focus of this research is to analyze and describe the philosophy of Javanese culture contained in Sri Wintala Achmad’s novel Zaman Gemblung. This research is included in the type of qualitative descriptive research. The data collection technique used is a literature study technique. Based on the results of the research study, it can be concluded that in the novel Zaman Gemblung by Sri Wintala Achmad the Javanese cultural philosophy is contained as follows: (1)Javanese speech cultural philosophy, (2) Javanese written cultural philosophy, and (3) Javanese written cultural philosophy. The three Javanese cultural philosophies can be used as a guide in living life at this time. As described in the novel, the philosophy of life of Javanese culture is synonymous with the view of life of the Javanese who always yearn for safety and prosperity, in Javanese terms memayu hayuning bawana.